Andean potato diversity conserved in the International Potato Center genebank helps develop agriculture in Uganda: the example of the variety ‘Victoria’ - Bernal-Galeano, V.; Norton, G.; Ellis, David; Anglin, Noelle L.; Hareau, Guy; Smale, Melinda; Jamora, Nelissa; Alwang, J.; Pradel, W. (Springer, 2020)
The International Potato Center (CIP) genebank conserves and facilitates access to highly diverse germplasm of potato, sweetpotato, and Andean roots and tubers as a global public good for food security. While it is generally understood that material from the CIP genebank has played an important role in the release of many CIP-related varieties grown by smallholder farmers in lower-income countries, the contribution has not been evaluated in quantitative terms. By applying the relative contribution of provenance based on pedigree data, we apportion the CIP genebank contribution of two released potato varieties: Pallay Poncho and Victoria. The estimated contribution of the CIP genebank to Pallay Poncho and Victoria is 35% and 72%, respectively. We then used an economic surplus approach to measure Victoria’s benefits in Uganda by attributing and valuing productivity gains. The gross benefit of Victoria in Uganda is estimated at USD $1.04 billion (2016 value), which exceeds the annual operating cost of the entire genebank over its lifetime. Seventy-two percent of the economic benefits corresponding to germplasm of Victoria are due to the CIP genebank contribution. Our findings demonstrate the magnitude of economic benefits generated by the use of conserved germplasm provided by the CIP genebank in crop improvement, which is only one of the several components of its total economic value. These results show that the availability of diverse germplasm is perhaps one of the most important elements in varietal development.